2023
DOI: 10.1097/bot.0000000000002578
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Supplemental Medial Buttress Plate Fixation for High-Energy Displaced Femoral Neck Fractures in Young Adults

Abstract: Objectives: To evaluate whether augmenting traditional fixation with a femoral neck buttress plate (FNBP) improves clinical outcomes in young adults with high-energy displaced femoral neck fractures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…The surgical management of displaced femoral neck fractures in young and middle-aged patients is fraught with challenges and high rates of treatment failure despite recent developments in surgical strategies and techniques. 1–7 A recent report on clinical outcomes using the database evaluated in this study showed that complications and treatment failure remain extremely common in this patient population. 1 An ongoing area of interest for surgeons tasked with managing these injuries is whether the choice of fixation influences the likelihood of treatment failure.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…The surgical management of displaced femoral neck fractures in young and middle-aged patients is fraught with challenges and high rates of treatment failure despite recent developments in surgical strategies and techniques. 1–7 A recent report on clinical outcomes using the database evaluated in this study showed that complications and treatment failure remain extremely common in this patient population. 1 An ongoing area of interest for surgeons tasked with managing these injuries is whether the choice of fixation influences the likelihood of treatment failure.…”
Section: Introductionmentioning
confidence: 85%
“…1 An ongoing area of interest for surgeons tasked with managing these injuries is whether the choice of fixation influences the likelihood of treatment failure. 1,2,5,[8][9][10][11] Historical constructs for the management of these injuries have typically included a fixed-angle (FA) device (ie, sliding hip screw [SHS] or the use of multiple cannulated screws [MCS]). More recent reports have emphasized the addition of socalled antirotation (AR) screws or femoral neck buttress plate Accepted for publication April 26, 2024.…”
Section: Introductionmentioning
confidence: 99%
“…A multicentre study, led by surgeons from Fort Worth (Texas, USA) , included patients from 27 North American level one trauma centres, and the authors examined the outcomes of 478 patients aged younger than 55 years. 5 The cohort were all treated operatively following presentation with a displaced femoral neck fracture. As would of course be expected from a retrospective study of this nature, the groups were not even, and 11% (n = 51) also had the fixation augmented with a femoral neck buttress plate.…”
Section: Young Hip Fractures: Is a Medial Buttress The Answer?mentioning
confidence: 99%